(untitled) (Research, Society and Development, 2022)
The use of pesticides to protect crops is a common practice in agribusiness. However, in addition to being necessary to minimize the environmental impacts associated with this practice, it is also of paramount importance that global workers be calculated so that there are no impacts on occupational health. In this context, this article aimed to evaluate the deposition of pesticides on the applicator during the preparation and application of the syrup under standardized conditions and in adverse conditions of wind and leakage. The experiment was carried out in a greenhouse, evaluating the application of two pesticides with a manual costal sprayer and a full cone-shaped jet tip. To assess the deposition of the products on the applicator, water-sensitive paper labels were used, on the PPE, positioned on 28 parts of the body. The results showed that all parts of the body evaluated were affected by pesticides. Wind is also a relevant meteorological parameter for increasing the deposition of pesticides on the applicator, as well as accidental grout leaks. It is concluded that the application of pesticides through the use of back spray requires the use of PPE capable of neutralizing the exposure to chemical agents for all parts of the applicators’ bodies, in order to promote adequate occupational safety and impact wind power also enhances drift and the consequent increase in the deposition of pesticides on the applicator.